Peptide transport in yeast: utilization of leucine- and lysine-containing peptides by Saccharomyces cerevisiae. - Marder, R (1977)
A variety of leucine-containing di- and tripeptides and two lysine-containing dipeptides supported the growth of strain Z1-2D, a leucine, lysine auxotroph of Saccharomyces cerevisiae. However, (Lys)2, (Lys)3, (Lys)4, and (Lys)5 as well as Gly-Leu-Gly, three tetra- and one pentapeptide containing leucine were not utilized by the mutant. Cellular peptidases released leucine or lysine from all of these non-growth-supporting peptides, suggesting that the failure of strain Z1-2D to utilize these compounds reflects their failure to enter the yeast. Competition studies employing phenylalanine or non-leucine-containing peptides showed that the uptake of peptides into S. cerevisiae Z1-2D is distinct from that of amino acids and that di- and oligopeptides may share a common transport system. The failure of strain Z1-2D to utilize any peptide larger than (Leu)3 may indicate a transport size limit. Such a size limit would influence the construction of models that explain the action of yeast mating factors.